IoT-Based Watering, Control, and Monitoring System for Tomato Plants Using Wemos D1 Mini - Henny Pramita Sari; Hakim, Lukman (Journal of Technomaterial Physics, 2022)
The growth of plant tomatoes is influenced by several factors, such as temperature, humidity, land, and rain. This study aimed to design the watering, control, and monitoring system for plants tomatoes with IoT-based using Wemos D1 Mini. The equipment is designed for sprinkling the plant tomatoes in a pot based on the response of a capacitive soil moisture sensor. The temperature was monitored using the DS18B20 sensor, and the presence of rain was determined using the raindrop sensor. On top of the equipment, an automatic on-off roof was built. This equipment was integrated with the website ofÂ  Thingspeak and the Blynk application. The test results show that the design in this study could control the pump based on soil humidity with a control value of 60%. Furthermore, the built roof automatically works when detecting the temperature (higher or lower than 28Â°C) and the presence of rain.